2022
DOI: 10.1155/2022/1093358
|View full text |Cite|
|
Sign up to set email alerts
|

The Media Public Opinion Analysis on the Implementation of “Double Reduction” Policy in Education Based on Big Data

Abstract: Monitoring the internet media opinion information quickly triggered by the implementation of the “double reduction” policy, and identifying the hot spots, tendencies, communication trends, and characteristics of media opinion are of great significance to government departments to grasp the dynamics of media opinion in time and assist them in decision-making. This paper uses the web crawler to dynamically collect the internet media opinion big data related to the “double reduction” of main media and utilizes te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…At the present stage in China, the policy of “double reduction” is one of the main topics for numerous discussions, disputes and arguments, which are based on the wide dissemination of information in the media. According to Li et al (2022), most students, parents, and teachers in China are aware of the “double reduction” policy, and various researchers share their views on the impact of the policy on student academic achievement. These scholars also note that in September and October 2021, the media significantly increased coverage of these public policies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the present stage in China, the policy of “double reduction” is one of the main topics for numerous discussions, disputes and arguments, which are based on the wide dissemination of information in the media. According to Li et al (2022), most students, parents, and teachers in China are aware of the “double reduction” policy, and various researchers share their views on the impact of the policy on student academic achievement. These scholars also note that in September and October 2021, the media significantly increased coverage of these public policies.…”
Section: Discussionmentioning
confidence: 99%
“…Mikesell (2021), in his article "The "Double Reduction" Crackdown and the Future of Private Education in China," also discusses the features of the "double reduction" policy and concludes that this policy did not bring significant changes to the daily lives of students, but it negatively affected the private the tutoring sector, which was forced to change its profile in the new environment and find new earning opportunities. Li et al (2022) in their work "The Impact of the Double Reduction Policy" characterize the policy of "double reduction," consider its background, and also pay special attention to the problems of the impact of this policy on micro and mesosystems. This research work is aimed at studying the features of the "double reduction" policy, its advantages and disadvantages, as well as its impact on the educational processes of Chinese students studying in European educational institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Around the world and China, the double reduction policy is a hotly observed, discussed and contested topic in the country based on media dissemination of information. According to Li et al (2022), different stakeholders have contributed their opinions related to the policy on students' academic performance and parents decision for their wards. The authors noted that media outlets in China showed increased reporting on the double reduction policy in September and October 2021.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other academics look into the public's perception based on big data to learn about people's concerns over the enforcement of the 'double reduction' policy. According to Li et al, the public is more aware of initiatives for carrying out the 'double reduction' policy, the results, impacts and appraisal of the application of the policy, as well as new problems and phenomena that result from its use [9]. Similarly, Jia and Peng identify four aspects frequently discussed on the internet including 'institutional supervision', 'industry impact', 'policy implement' and 'public feedback' [10].…”
Section: Impact Of 'Double Reduction' Policymentioning
confidence: 99%
“…Although restricted by the initiatives, off-campus training institutions do not completely eliminate from the market. All kinds of implicit channels are surging, such as one-to-one tutors, live-in nannies and group-funded teachers (usually a group of students hire famous teachers to teach) [8][9][10][11]. This not only puts more financial strain on parents but also destroys the educational system, and makes the problem of educational inequality worse.…”
Section: Impact Of 'Double Reduction' Policymentioning
confidence: 99%